Visceral Leishmaniasis: Advancements in vaccine development via classical and molecular approaches - Sumit eJoshi; Keerti eRawat; Narendra Kumar Yadav; Vikash eKumar; Mohammed Imran Siddiqi; Anuradha eDube (Frontiers in Immunology, 2014)
Visceral Leishmaniasis (VL) or kala-azar, a vector-borne protozoan disease, shows endemicity in larger areas of the tropical, subtropical and the Mediterranean countries. WHO report suggested that nearly 500,000 new cases of VL occur annually, including 100,000 cases from India itself. Treatment with available anti-leishmanial drugs are not cost effective, with varied efficacies and higher relapse rate, which poses a major challenge to current kala-azar control program in Indian subcontinent. Therefore, a vaccine against VL is imperative and knowing the fact that recovered individuals developed lifelong immunity against re-infection, it is feasible. Vaccine development program, though time taking, has recently gained momentum with the emergence of omic era i.e. from genomics to immunomics. Classical as well as molecular methodologies has been overtaken with alternative strategies wherein proteomics based knowledge combined with computational techniques (immunoinformatics) speed up the identification and detailed characterization of new antigens for potential vaccine candidates. This may eventually help in the designing of polyvalent synthetic and recombinant chimeric vaccines as an effective intervention measures to control the disease in endemic areas. This review focuses on such newer approaches being utilized for vaccine development against VL.